The role of inflammation in Ischemic stroke: from biomarker to treatment - Xiao, Liangyi; Huang, Yini; Wu, Lingying; Zeng, Shanshan; Qiu, Changjiang; Li, Xing; Xie, Le; Wu, Dahua (Frontiers in Immunology, 2025)
Stroke ranks among the most prevalent diseases globally. Ischemic stroke (IS), constituting 87% of all strokes, poses a significant threat to patients’ health. Following the onset of IS, within a few minutes, inflammation is initiated. This inflammation activates immune cells and related signaling pathways, further exacerbating the inflammatory state, eventually leading to irreversible brain injury. Therefore, regulating the inflammatory response can contribute to the treatment of IS. This review delves into the inflammatory mechanism in IS, the role of inflammatory markers, and the research advancements regarding the use of inflammatory markers in treatment. While previous studies often concentrated on a single aspect of the inflammatory mechanism or specific inflammatory markers, this review systematically synthesizes the fragmented information. It offers readers a comprehensive and coherent view, facilitating an in - depth comprehension of the complexity of the inflammatory response in IS. This article not only expounds the value of inflammatory markers in disease diagnosis and prognosis, but also highlights the research progress including traditional Chinese medicine treatment. This has important guiding significance for clinicians to formulate precise treatment plans, and provides a variety of options for clinical practice. The research progress of these treatment strategies presents new opportunities for addressing the challenges in IS treatment, with the potential to improve patients’ prognosis and quality of life. Through a comprehensive overview of inflammation - related studies in IS, this review serves as a valuable reference for research and clinical practice in this field, contributing to the further development of IS treatment research.